The content of total protein and ethereal extract of grains of soy varieties from different locals of production evaluation (Research, Society and Development, 2022)
The aim of this work was having evaluated the total protein content and ethereal extract about the quality of soy grains and seeds to produce vegetable oil and bran in several varieties produced in two cities: Ilha Solteira, São Paulo state and Chapadão do Sul, Mato Grosso do Sul state, in the agricultural year 2018/19. In some samples, a template of seeds used at the seeding was also analyzed. Only one determination for each procedure and variety was done. Since there isn’t repetition per variety, the results were showed in histogram form. Because of the results obtained, it was checked that in general, the grains produced in Ilha Solteira city were displayed with the biggest contents of total protein; at the evaluated seeds in Chapadão do Sul city it was found the biggest contents of ethereal extract. Besides that, an inverse association could be observed among total protein content and oil in grains/seeds, but for the varieties TEC 7548 I, when produced in Chapadão do Sul. The varieties ANTA 82 RR and Desafio RR showed off with high levels of total protein, when sown in Ilha Solteira and Chapadão do Sul.